Academic Advising is a conceptual introduction - DJABALLAH, Khalfallah; AYAT, Lamine (Social Sciences Journal, 2021)
Academic guidance is an essential and pivotal pillar of the educational system, as it is an objective response to social, economic and humanitarian variables at the heart of the system and its educational philosophy, as well as responding to the needs of the student to communicate with university education. Academic guidance is central to the mentoring process: the educational institution and the student, reinforced by the role of a competent academic guide who works through the Academic Guidance Unit throughout the academic year. The academic guidance process is integrated with awareness and understanding of all parties to the mentoring process, with the aim of guiding the student to the most appropriate ways to choose the best ways to achieve the desired success and adapt to the university environment.